Mediating and examining expansive learning in the context of multidimensional complexities affecting household food security activity systems in Nyanyadzi Irrigation Scheme in the Manicaland Province of Zimbabwe - Mukwambo, Robson (Rhodes University, Faculty of Education, Department of Education)
The study sought to mediate and examine expansive learning in the context of multidimensional complexities affecting household food security activity systems in Nyanyadzi Irrigation Scheme in Ward 8 of Chimanimani District in the Manicaland province of Zimbabwe. Therefore, the main foci of the study were to investigate how multidimensional complexities have come to be the way they are (historicizing) and how they enable or constrain learning of household food production. The study utilized Cultural Historical Activity Theory and the Expansive Learning Cycle (Engeström & Sannino, 2010) to examine and mediate collective learning in response to the multidimensional complexities and also to contribute to transforming the farmers' activity systems towards more sustainable practices to ensure household food security. The study used a qualitative research approach, utilizing an insider formative intervention approach in a case study design in which Nyanyadzi irrigation scheme was the case study. I have adopted the insider formative interventionist role as a 3rd generation farmer, born and bred in Nyanyadzi area, and my family has been involved in the Nyanyadzi irrigation scheme for three generations. I see this as synergistic with the need for deep cultural understanding in CHAT research. However, this role also provided challenges for me to maintain a rigorous approach to the research in which I also reflexively review my own role and influence in the research process. Following CHAT expansive learning methodological guidance, data was generated through fifteen (15) face to face interviews with three generations of farmers in the scheme (historical ethnographic data); four focus group discussions (contemporary ethnographic data) and eight (8) sessions in a three (3) day change laboratory workshop (expansive learning data). Double stimulation and 'mirror' data was used to surface and prioritise responses to contradictions in the Change Laboratory Workshops (CLW), which is a methodology developed in and for CHAT research (ibid). The data was analysed using both inductive and abductive approaches and were conducted in a three-phased process focusing firstly on the history of the object, followed by current perspectives on the object of activity and lastly on transformations emerging in the object of activity via the expansive learning process. Cultural Historical Activity Theoretical tools informed activity system analysis and analysis of the history of the object and emerging contradictions; and the expansive learning cycle (ELP) process framework associated with and emergent from CHAT was used to analyse the emergence of transformative agency and expansion of the object. Four levels of contradictions were used to describe and explain the emergent contradictions namely, primary, secondary, tertiary and quaternary contradictions and are presented in this sequence as catalytic opportunities for expansive learning as proposed in CHAT. In addition, the four types of discursive manifestations of contradictions namely, dilemma, conflict, critical conflict and double bind were used to describe and explain the manifestations of contradictions in this study and their role in catalysing transformative agency. The concept of linguistic cues for discursive manifestations of contradictions was adopted and employed in the preliminary data analysis phase. In addition, the transformative agency expressions and zone of proximal development (ZPD) concept was applied in and to the CLW data to examine the learning pathways and to co-develop and expand farmers' and other stakeholders' transformative agency and ZPD respectively. I found myself as formative insider researcher having to take on a strong role as co-engaged researcher / participant in the irrigation scheme expansive learning process. The study concluded that the farmers' activity system is the central activity system and it interacts with other activity systems on a partially shared object "improved crop production and marketing under irrigation scheme" . Through interactions with other neighbouring activity systems, the farmers have faced multidimensional complexities that constrain their ability to fully realise their object. These multidimensional complexities manifest in three critical contradictions as a critical conflict in leadership and management crisis; a dilemma and double bind in a lack of farmer education and training; and lastly, a dilemma and double bind in poor crop marketing. These multidimensional complexities have a historical account and they have evolved in complexity over time and I argue in the thesis that, a careful cultural-historicity of the object of activity and mediation of the situated learning can help to collectively come up with solutions to these multidimensional complexities. The study further concluded that despite these multidimensional complexities in the scheme, learning has been taking place and such learning was sometimes mediated through demonstrations as "learning by doing," "seeing is believing" and the "winners and losers" concept. Furthermore, through the CLW process the farmers and other stakeholders' cognitive horizons were expanded by the mirror data and double stimulation processes, and the expansive learning process developed their individual and collective transformative agency pathways and expanded their collective zone of proximal development. In this study I argue that there has been little said about collective learning in irrigation schemes and given the dearth of detail on such learning, it seems that this learning is either going unnoticed or is ignored. Hence, I further argued that the multidimensional complexities in irrigation schemes are both a stimulant for learning and provide a space (object) for collective learning, as was also shown by Baloi (2016). The study also shows that the collective learning potential in these irrigation schemes can be pro-actively mediated via expansive learning formative interventions in support of improved crop production and marketing for produce developed under irrigation in irrigation schemes such as the Nyanyadzi Irrigation scheme. Lastly, being an insider formative interventionist researcher in this study, with intergenerational engagement and perspective on the history of the object and integrational engagement with the transforming object, I became part of the intergenerational transformation of the irrigation scheme's object. The intergenerational co-construction of the history of the object, coupled with the insider formative interventionist researcher approach opened up and allowed me as a current generation agent or actor to develop an in-depth understanding of the multidimensional nature and historicity of the object. This was crucial for opening up the transformative agency pathways. It also produced a responsibility for me as an insider formative interventionist researcher to carry the summative findings of the study back into the social context to widen the engagement and mediation of the transformation needed in the community. Overall not only does the study offer an intergenerational perspective on multidimensional complexities of the object and how this can generatively be mobilised via expansive learning into emerging transformative learning agency pathways, but it also offers a new vantage point on the role of the insider formative interventionist researcher. Through this, the study offers insight into how we as third generation members of the community can be brought closer to our communities through the application of our skills, thereby also offering a new type of engaged and rigorously framed and executed research with roots in our communities. As shown in this study, not only does this expand the knowledge and experience of those we engage with, but it also expands our own knowledge and expertise in order to be more able to contribute to both the challenges of our own communities but also that of other communities and situations similar to ours, and beyond these bounded contexts. The study's contribution is both practical, but also methodological from this vantage point, especially in an African context where there is much critique of 'outsider research', yet little pro-active articulation of what insider (in this case, formative intervention) research may look like.,Thesis (PhD) -- Faculty of Education, Education, 2021
Keywords: Active learning -- Zimbabwe -- Chimanimani District; Food security -- Zimbabwe -- Chimanimani District; Sustainable agriculture -- Zimbabwe -- Chimanimani District; Irrigation farming -- Zimbabwe -- Chimanimani District; Qualitative research; Cultural-historical activity theory (CHAT); Nyanyadzi Irrigation Scheme